Relationship between Vitiligo Disease and Quality of Life of Patients at Sanjiwani Gianyar Regional General Hospital - Prasanthi Dewi, Ratih; Puspasari, Ni Made Indah; Sumadewi, Komang Trisna (Muhammadiyah Medical Journal, 2025)
Background: Vitiligo is an idiopathic skin disorder of acquired depigmentation that burdens patients’ lives. This disorder often causes problems that can affect the psychological and social well-being of patients and ultimately affect their quality of life. Purposes: This study aims to determine the relationship between vitiligo disease and patients’ quality of life at Sanjiwani Gianyar Hospital. Methods: This type of research is analytically observational with a cross-sectional approach. Data were collected by filling out the DLQI questionnaire. All data collected was analyzed using univariate and bivariate analysis. The research results are declared significant if the p-value is <0.05 and not significant if the p-value is >0.05. Results: The results showed that most vitiligo patients were in the age range of 30-39 years (30%), female (26%), high school education level (28%), unmarried (38%), self-employed and traders (20%), and generalized vitiligo classification (80%). The PR value of 3.33 (95% CI: 1.614-6.879) indicates vitiligo patients have at least a moderate to considerable influence on their quality of life by three times and at most six times. Based on the results of bivariate statistical tests using chi-square, the p-value = 0.000 (p < 0.05), which means the result is significant. Conclusion: Vitiligo disease is significantly related to patients' quality of life at Sanjiwani Gianyar Regional General Hospital.